THE INFLUENCE OF CARIBBEAN COLONIES ON EUROPEAN WOMENS FASHION AT THE END OF THE XVIII CENTURY AND BEGINNINGS OF XIX - Malagon-Mancebo, Massiel (Temas Americanistas, 2023)
Neoclassical fashion defined its diaphanous look by seeking to revive the style of the ancient Roman civilization, and the marble statues of ancient Greece; further influenced by the excavation of Pompeii in 1738 and its archeological developments in 1748. The attitudes towards voluminous and pompous fashions had changed, however the acceptance of the new modern and much more revealing silhouette did not occur without challenges. For neoclassical fashion to be accepted it needed a foundation to make it plausible, and it needed a pioneer to wear and deem it ‘appropriate’. This study builds a comprehensive analysis of some of the relationships France, England and other European countries built with their colonies in terms of textile manufacturing, imports and exports, and most importantly cultural appropriation. This study seeks to analyze how those colonies gave them new fashion perspectives, to develop the neoclassical fashions, we recognize from that period. In addition, this study will analyze the powerful influence of Josephine Bonaparte and other important female figures from neoclassical France, in perpetuating and expanding the use of these fabrics and styles; most importantly Josephine’s Caribbean background and her possible preference for lighter fabrics due to her birth on the island of Martinique, and how that influenced her sophisticated and cosmopolitan approach to fashion.